Youtube Bassed Learning Media Innovation In SKI Lesson in MIN 3 Ciamis - Darojat, Jajat; Amini, Ulfah; Sarip, Hasan; Asyari, Hobir; Yusuf, Iqbal Anggia; Badrudin, Badrudin; Zaqiyah, Qiqi Yuliati (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2024)
One of the strategic efforts in creating quality education is by innovating learning media. From the results of research investigations and observations, it was found that SKI learning is one of the monotonous subjects, because it is delivered through lectures. One of the subjects that contains historical material, so a competent teacher is needed in explaining SKI material. Through this research, researchers see the factor of media innovation that has not been fully used in SKI learning. This research uses qualitative research methods with the type of field research. It is a field study which is the main source in this research is the results of observations and interviews in the field. The results of this study are that before using YouTube-based learning media or using the lecture method, students' understanding of SKI material has not reached the expected understanding of the minimum completeness criteria in SKI learning subjects. From the results of oral and written tests, it was found that 20% of 16 students understood the material well, while the other 80% had not reached the minimum criteria for SKI learning. After making innovations to the learning media, the level of student understanding increased from 16 students, 10 of whom got the minimum completeness predicate. This means that 70% of the total number of students reached a good level of understanding, while the other 30% were still at an understanding below the minimum completeness.